2014
DOI: 10.1007/s13277-014-1936-7
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal FHIT protein expression may be correlated with poor prognosis in gastric cancer: a meta-analysis

Abstract: Our current meta-analysis is aimed to investigate the relationships between fragile histidine triad (FHIT) protein expression and prognosis in gastric cancer patients. We searched MEDLINE (1966 ~ 2013), the Cochrane Library Database (Issue 12, 2013), EMBASE (1980 ~ 2013), CINAHL (1982 ~ 2013), Web of Science (1945 ~ 2013), and the Chinese Biomedical Database (CBM) (1982 ~ 2013) without any language restrictions. The meta-analysis was conducted using the STATA 12.0 software. Crude hazard ratios (HR) with its 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Several investigators have shown that loss of FHIT function in preneoplastic lesions can lead to the accumulation of DNA damage and cell transformation; therefore it is defined as the guardian of the preneoplastic genome (12)(13)(14). Aberrant FHIT expression caused by truncated transcripts or promoter region hypermethylation has been found in esophageal, stomach, and colon carcinomas (7,15). Lack of FHIT expression in several studies was demonstrated to have impact on tumor aggressiveness (16).…”
Section: Introductionmentioning
confidence: 99%
“…Several investigators have shown that loss of FHIT function in preneoplastic lesions can lead to the accumulation of DNA damage and cell transformation; therefore it is defined as the guardian of the preneoplastic genome (12)(13)(14). Aberrant FHIT expression caused by truncated transcripts or promoter region hypermethylation has been found in esophageal, stomach, and colon carcinomas (7,15). Lack of FHIT expression in several studies was demonstrated to have impact on tumor aggressiveness (16).…”
Section: Introductionmentioning
confidence: 99%
“…FHIT loss was observed in 64% of non-small-cell lung cancer patients and was significantly associated with squamous cell carcinoma and poor tumor grade [10]. In addition, aberrant transcripts of FHIT have been found in other kinds of tumors, such as gastric [11], esophageal [12], and colon carcinomas [13]. FHIT has been recently seen as a genome caretaker which is of great importance for genome stability.…”
Section: Introductionmentioning
confidence: 99%
“…In this group of large CFS genes, FHIT and PARK2 have been demonstrated to function as important tumor suppressors involved in the development of many different cancers [18] , [19] . Decreased FHIT expression has been shown to be associated with tumor progression in sporadic colon adenocarcinoma and poor prognosis in gastric cancer and oral squamous carcinoma [20] , [21] , [22] . PARK2 is commonly downregulated in clear-cell renal carcinoma and is associated with aggressive disease and a poor clinical outcome [23] .…”
Section: Discussionmentioning
confidence: 99%